Analisis Hukum Perlindungan Perempuan dan Anak Terhadap Kasus Kekerasan dan Pembunuhan Kepada Perempuan dan Anak di Indonesia - Nurhakim, Abdul Aziz (CV WAHANA PUBLIKASI, 2023)
The fact is that now in social life, both individuals and groups, there are often deviations from the norms of social life, especially what are called legal norms. The increase in criminal activity in Indonesia continues to be a topic of conversation in society, criminal acts often develop, ranging from seemingly trivial theft to rape and murder. As we know, the crime of murder is a very terrible case that causes the loss of a person’s life. In 2021, there will be at least 1.076 cases in Indonesia due to the crime of murder. The victims of this murder are various ages and male or female. Nowadays, many people are wondering how we can identify and distinguish cases of murder against women and children. This research method uses a normative legal research/writing type, using a statutory approach, a case approach and a historical approach These killings usually start with a small conflict that continues to become a large one that continues for a long time. What constitutes evidence is listed in the KUHAP itself, there is an article that states what types of evidence are, namely in article 100 and 84 of the KUHAP, namely; witness statements, expert statements, letters, instructions and defendant statements. Factors that cause premeditated murder or ordinary murder include family, economic and environmental factors. Therefore, carry out socialization regarding criminal acts and the sanctions imposed by law.